Designing Digital Work Concepts and Methods for Human-centered Digitization - Oppl, Stefan; Stary, Christian (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
"This book could well be the most comprehensive collection to date of integrated ideas on the elicitation, representation, integration and digitization of work processes and collaboration. The authors take a heavily human-centered approach while never losing sight of engineering aspects involved. Rooted in relevant theories, they present a set of practice-oriented tools and methods that will help bring work and work support into the hyper connected, data-driven era we are now entering." Stijn Hoppenbrouwers, Professor, HAN University of Applied Sciences, the Netherlands and Radboud University, the Netherlands Combining theory, methodology and tools, this open access book illustrates how to guide innovation in today's digitized business environment. Highlighting the importance of human knowledge and experience in implementing business processes, the authors take a conceptual perspective to explore the challenges and issues currently facing organizations. Subsequent chapters put these concepts into practice, discussing instruments that can be used to support the articulation and alignment of knowledge within work processes. A timely and comprehensive set of tools and case studies, this book is essential reading for those researching innovation and digitization, organization and business strategy.